Pengembangan Perikanan Budidaya: Efektivitas Program Minapolitan Dalam Pengelolaan Perikanan Budidaya Berkelanjutan di Kabupaten Gresik - Zakiyah, Dwi Maulidatuz (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Aquaculture is one of activities developed in Gresik. However, itâ€™s pressing the ecosystem of coastal area with the high mangrove destruction due to expansion of the pond and a wide variety of negative impacts for environment. The government implemented minapolitan program to increase the productivity of aquaculture to be able to improve the well-being of coastal communities. Therefore, question on this research is â€œhow minapolitan program effectiveness in the management of sustainable aquacultureâ€. The method of research is qualitative with intention to understand the activities of aquaculture and its influence on economic, social and environment condition in Gresik. To answer the research question, it is conducted field surveys, interviews and questionnaires to the farmers. To determine effectiveness of the minapolitan program, the author evaluate the sustainability of aquaqulture activities. The results showed that aquaculture provides a wide range of positive and negative impacts for the economic, social and environment condition. Furthermore, based on the assessments of the sustainability, it can be Â seen that the minapolitan program failed Â and Â ineffective Â in Â realizing Â the Â sustainable development Â of aquaculture. This is due to the lack of continuity and the balance of the three aspects of sustainable development (economic, environmental and socio-territorial).